Comparative growth performance and proteolytic enzyme activity of Indian major carp larvae, fed with live food and refrigerated-plankton food - SHARMA, J G; CHAKRABARTI, R (The Indian Journal of Animal Sciences, 2011)
Indian major carp Catla catla (0.79±0.01 mg) larvae were cultured under 2 feeding regimes of live food (LFS) and refrigerated-plankton food (RPFS) in recirculating systems separately for 30 days. Survival of larvae was 18% higher in LFS compared to RPFS. Final average weight was significantly higher in fish fed with live food compared to the refrigerated-plankton fed fish. Specific growth rate was significantly higher in former compared to latter one. RNA/ DNA of catla was nearly two-fold higher in live food fed fish compared to the refrigerated-plankton food fed fish. Food was utilized in a better way in LFS compared to RPFS is evident from the significantly lower value of FCR in the former compared to the latter system. Specific proteolytic activity was significantly higher in LFS (0.82±0.02 mg tyrosine/mg protein/h) compared to RPFS (0.457±0.01 mg tyrosine/mg protein/h). The presence of more digestive enzymes, especially proteolytic enzyme in live food fed catla resulted into the proper digestion of ingested food compared to the fish fed with refrigerated-plankton food. Prevalence of better water quality in terms of significantly lower values of ammonia, nitrite, phosphate and COD in LFS compared to the RPFS was conducive for the better performance of catla in the former feeding scheme. Reduction in nutrient contents like protein and lipid as well as leaching of essential nutrients especially free amino acids from refrigerated-plankton may be responsible for the poor performance of catla larvae in RPFS compared to LFS.